Proving Equivalence using Truth Tables: p ∧ (q ∨ r ) ≡ (p ∧ q) ∨ (p ∧ r ), and p ∨ (q ∧ r ) ≡ (p ∨ q) ∧ (p ∨ r )

p ∧ (q ∨ r ) ≡ (p ∧ q) ∨ (p ∧ r )p ∨ (q ∧ r ) ≡ (p ∨ q) ∧ (p ∨ r )

To prove the first equation, p ∧ (q ∨ r ) ≡ (p ∧ q) ∨ (p ∧ r):

We will use the truth table method to prove the equivalence

To prove the first equation, p ∧ (q ∨ r ) ≡ (p ∧ q) ∨ (p ∧ r):

We will use the truth table method to prove the equivalence.

Truth Table for p ∧ (q ∨ r ):

| p | q | r | q ∨ r | p ∧ (q ∨ r ) |
|—|—|—|——-|————–|
| T | T | T | T | T |
| T | T | F | T | T |
| T | F | T | T | T |
| T | F | F | F | F |
| F | T | T | T | F |
| F | T | F | T | F |
| F | F | T | T | F |
| F | F | F | F | F |

Truth Table for (p ∧ q) ∨ (p ∧ r ):

| p | q | r | p ∧ q | p ∧ r | (p ∧ q) ∨ (p ∧ r ) |
|—|—|—|——–|——-|——————|
| T | T | T | T | T | T |
| T | T | F | T | F | T |
| T | F | T | F | T | T |
| T | F | F | F | F | F |
| F | T | T | F | F | F |
| F | T | F | F | F | F |
| F | F | T | F | F | F |
| F | F | F | F | F | F |

By comparing the two truth tables, we can see that the values for p ∧ (q ∨ r ) and (p ∧ q) ∨ (p ∧ r ) are the same for all possible combinations of truth values for p, q, and r. Therefore, we can conclude that p ∧ (q ∨ r ) ≡ (p ∧ q) ∨ (p ∧ r ).

To prove the second equation, p ∨ (q ∧ r ) ≡ (p ∨ q) ∧ (p ∨ r ):

Again, we will use the truth table method.

Truth Table for p ∨ (q ∧ r ):

| p | q | r | q ∧ r | p ∨ (q ∧ r ) |
|—|—|—|——-|————–|
| T | T | T | T | T |
| T | T | F | F | T |
| T | F | T | F | T |
| T | F | F | F | T |
| F | T | T | T | T |
| F | T | F | F | F |
| F | F | T | F | F |
| F | F | F | F | F |

Truth Table for (p ∨ q) ∧ (p ∨ r ):

| p | q | r | p ∨ q | p ∨ r | (p ∨ q) ∧ (p ∨ r ) |
|—|—|—|——–|——-|——————|
| T | T | T | T | T | T |
| T | T | F | T | T | T |
| T | F | T | T | T | T |
| T | F | F | T | F | F |
| F | T | T | T | T | T |
| F | T | F | T | F | F |
| F | F | T | F | T | F |
| F | F | F | F | F | F |

Again, by comparing the two truth tables, we can see that the values for p ∨ (q ∧ r ) and (p ∨ q) ∧ (p ∨ r ) are the same for all possible combinations of truth values for p, q, and r. Therefore, we can conclude that p ∨ (q ∧ r ) ≡ (p ∨ q) ∧ (p ∨ r ).

More Answers:

Proving the Equivalence of Logical Statements using De Morgan’s Theorem and the Distributive Law in Math
Logical Equivalence Proof: Commutative Property of Conjunction and Disjunction
Exploring the Laws of Boolean Algebra: Proving Equations using Associative Law

Error 403 The request cannot be completed because you have exceeded your quota. : quotaExceeded

Share:

Recent Posts

Mathematics in Cancer Treatment

How Mathematics is Transforming Cancer Treatment Mathematics plays an increasingly vital role in the fight against cancer mesothelioma. From optimizing drug delivery systems to personalizing

Read More »